Leveraging the synergy between anti-angiogenic therapy and immune checkpoint inhibitors to treat digestive system cancers - Xu, Qinlan; Shao, Dong (Frontiers in Immunology, 2024)
The response rates to immunotherapy vary widely depending on the type of cancer and the specific treatment used and can be disappointingly low for many solid tumors. Fortunately, due to their complementary mechanisms of action, immunotherapy and anti-angiogenic therapy have synergistic effects in cancer treatment. By normalizing the tumor vasculature, anti-angiogenic therapy can improve blood flow and oxygenation to facilitate better immune cell infiltration into the tumor and enhance the effectiveness of immunotherapy. It also reduces immunosuppressive factors and enhances immune activation, to create a more favorable environment for immune cells to attack the tumor. Their combination leverages the strengths of both therapies to enhance anti-tumor effects and improve patient outcomes. This review discusses the vasculature-immunity crosstalk in the tumor microenvironment and summarizes the latest advances in combining anti-angiogenic therapy and immune checkpoint inhibitors to treat digestive system tumors.